Appearance of medium–large drusen and reticular pseudodrusen on adaptive optics in age-related macular degeneration. Issue 11 (1st July 2014) - Querques, Giuseppe; Kamami-Levy, Cynthia; Blanco-Garavito, Rocio; Georges, Anouk; Pedinielli, Alexandre; Capuano, Vittorio; Poulon, Fanny; Souied, Eric H
Abstract : Purpose: To investigate the appearance of medium–large drusen and reticular pseudodrusen on adaptive optics (AO). Methods: In 14 consecutive patients, AO infrared (IR) images were overlaid with confocal scanning-laser-ophthalmoscope IR reflectance images and IR-referenced spectral-domain optical coherence tomography. Results: In eight eyes of six patients, a total of 19 images of medium–large drusen were investigated by AO imaging. En face AO revealed medium–large drusen as highly hyper-reflective round/oval lesions, always centred and/or surrounded by a continuous/discontinuous hyporeflectivity. Cone photoreceptors were detected overlying drusen, appearing either as continuous 'bright' hyper-reflective dots over a 'dark' hyporeflective background, or as continuous 'dark' hyporeflective dots over a 'bright' hyper-reflective background. In eight eyes from eight patients, a total of 14 images of pseudodrusen were investigated by AO imaging. En face AO revealed reticular pseudodrusen as isoreflective lesions, always surrounded by a continuous/discontinuous hyporeflectivity. Cone photoreceptors were detected overlying pseudodrusen as 'bright' hyper-reflective dots over either a hyporeflective or isoreflective background. No 'dark' hyporeflective dots were detected in eyes with reticular pseudodrusen only. Cone photoreceptors were counted on the border of the drusen and pseudodrusen, respectively, and in a visibly healthy zone in its absolute vicinity. A similar decrease in cone appearance was observed for drusen and pseudodrusen (15.7% vs 16.2%). Conclusions: AO allows differences in reflectivity between medium–large drusen and reticular pseudodrusen to be appreciated. The cone mosaics may be detected as continuous 'bright' hyper-reflective dots overlying/on the border of drusen and pseudodrusen deposits, and possibly as continuous 'dark' hyporeflective dots overlying drusen only.